The Effectiveness of Synchronous and Asynchronous E-Learning Environments in Teaching Writing to Different Personalities - Ajeng Hidayatul Maghdalena; Abdurrachman Faridi; Rudi Hartono (Universitas Negeri Semarang, 2022)
Since the Covid-19 pandemic is affecting the new educational environments, synchronous and asynchronous e-learning environments have been integrated into the teaching and learning process. This study aims to explain how significant the studentsâ€™ achievement is taught in e-learning environments in teaching writing to students with different personalities. The design of this study was a quasi-experimental design with a 2Ã—2 factorial design. This study was conducted on the eighth-grade students at SMP N 2 Mantup. The questionnaire and written test were carried out by t-test and two-way ANOVA. This study discovered a relationship between the e-learning environments and students' personalities, which influences their ability to write recount texts. This research showed that an asynchronous e-learning environment was effective for students with introverted personalities, and a synchronous e-learning environment was effective for students with extroverted personalities. This study also compared the use of the e-learning environments for each personality in improving writing recount text. Thus, this study presented a new perspective on the importance of paying attention to students' personalities in selecting the e-learning environments to improve writing recount text. The contribution of this study provided to the ELT development was new insight on how effective the teaching implemented in a dual mode digital environment is, no matter what personality the students possess. Thus, it is proven that modern teaching has no boundary, spatially and temporally.